Financial education in Asia: Assessment and recommendations - Naoyuki Yoshino; Peter J. Morgan; Ganeshan Wignaraja (Asian Development Bank Institute (ADBI), 2015)
This paper assesses the case for promoting financial education in Asia. It argues that the benefits of investing in financial education can be substantial. Data are limited, but indicate low financial literacy scores for selected Asian countries. As economies develop, access to financial products and services will increase, but households and small and medium-sized enterprises need to be able to use the products and services wisely and effectively. More effective management of savings and investment can contribute to overall economic growth. Moreover, as societies age and fiscal resources become stretched, households will become increasingly responsible for their own retirement planning. Asia's evolving experience suggests that more national surveys of financial literacy are needed and that coherent, tailored national strategies for financial education are essential for success.
Keywords: D14; D18; G21; G28; I25; L26; 330; financial education; financial literacy; education investment